PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCEMARAN LINGKUNGAN HIDUP (DI DESA PUSAR KECAMATAN BATURAJA BARAT KABUPATEN OGAN KOMERING ULU) - Olivia Sianura; M Tamudin (Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACT The background of this research is that cement mining activities by PT Semen Baturaja aim to meet the national demand for cement, especially in the South Sumatra region. This activity is actually in the context of fulfilling the State's duties in the welfare of the people, however this mining activity has an impact on the environment and the community around PT Semen Baturaja. Among the negative impacts are the reduced water reserves, the amount of dust caused by mining activities around Navel Village. This background inspired the writer to conduct research with the title